TELEWORK, WELL-BEING, STRESS, AND PRODUCTIVITY DURING COVID-19 PANDEMIC: DOES WOMEN'S RESILIENCE MATTER? - Anindita, Rina; Korompis, Veinne Nathasia (Universitas Brawijaya, Indonesia, 2022)
This study aims to analyze the relationship between perceived stress, psychological well-being and perceived productivity through teleworking with resilience as moderation for married female employees in the telecommunications network company in Jakarta. The data analysis method used was Structural Equation Modeling (SEM)–Partial Least Square (PLS) by distributing questionnaires to 148 married women employees. Data were collected from December 2021 to 2022 through an online questionnaire distributed through the human resources department. The results of this study supported the six hypotheses proposed, and 1 of the seven hypotheses did not. Perceived stress and teleworking have a relationship with psychological well-being. Moreover, teleworking can mediate the relationship between perceived stress and psychological well-being. Surprisingly women's resilience does not moderate the relationship between teleworking and psychological well-being. This study also revealed that perceived stress and psychological well-being are related to perceived productivity. This condition requires an active role of corporate leaders to find effective ways to deal with stress and increase well-being and employee productivity during teleworking or Work From Home. Corporate leaders must begin to design and plan better methods to support employees who have flexible working hours.